Dynamic susceptibility contrast perfusion MRI identifies persistent vessel pathology in acute pontine stroke - Förster, Alex; Ottomeyer, Caroline; Wolf, Marc; Kern, Rolf; Griebe, Martin; Gass, Achim; Hennerici, Michael G.; Szabo, Kristina (Cerebrovascular diseases, 2010)
Background: In large territorial stroke of the anterior and the posterior circulation, the extent of affected tissue can be characterized by the demonstration of vessel occlusion on MR angiography (MRA), while the extent of hypoperfusion can be shown on dynamic susceptibility contrast perfusion-weighted MRI (PWI). The ability of MRA and conventional MRI sequences to demonstrate branches of the basilar artery (BA) is very limited. This study analyzes the value of the combined use of diffusion-weighted MRI (DWI), MRA and PWI in acute pontine stroke. Methods: A series of 24 consecutive patients with acute pontine stroke received an extensive MRI stroke workup including DWI, PWI and MRA. Results: In 11/24 patients visual analysis of PWI demonstrated persisting hypoperfusion, and in 1/24 patients indication of hyperperfusion was found. Vessel abnormalities were seen in 19/24 patients (15/24 hypoplastic vertebral artery, 9/24 stenosis or occlusion of the BA, 1/20 ectatic BA). Persistent pontine hypoperfusion was more frequently associated with BA pathology (9/11 vs. 1/13, p = 0.001), large-vessel disease (8/11 vs. 1/13; p = 0.001) and a more pronounced clinical deficit (NIHSS score on day 1: 7 vs. 3, p = 0.01). Conclusions: In pontine ischemia areas of hypoperfusion can be identified due to the strong contrast induced by ischemia on PWI and can be easily related to DWI lesion size. This is of use particularly as small vessels are frequently missed by MRA and occlusion of the BA can be better characterized with the help of PWI.
Gesehen am 17.03.2021